Improving accuracy of breeding values by incorporating genomic information in spatial-competition mixed models [Conjunto de datos] - Cappa, Eduardo Pablo (2017)
Supplementary information of a Eucalyptus grandis population, genomic and pedigree data including identity information of trees, family, and provenance of the paper entitled: Improving accuracy of breeding values by incorporating genomic information in spatial-competition mixed models. Mol Breeding 37, 125 (2017).